A prestação de serviços extensionista na UFMG: das políticas às práticas - Cristofane da Silveira Queiroz (2018)
This thesis intends to analyze the extension services provided by the Federal University of Minas Gerais. This study is part of Education policy field research for public Universities. It aims to understand the provision of services from the State's inductive role along with the assimilation of both institutional policies and practices. The theoretical and epistemological background is based on Historical and Dialectical Materialism Theory. In order to analyze educational policies, I use the policy cycle approach. Bibliographical and documentary research, content analysis, as well as quantitative and qualitative approaches are used to understand and explain not only the policies that motivate the provision of services but also the characteristics and practices produced by the university. The provision of services is discussed within the scope of university extension since it is the realm of direct integration between university and society in general, university extension provides samples of the services performed at UFMG. Consequently, this study highlights that these services were originated by extension activities, constant elements in the history of Brazilian universities as an offspring of the close interaction of university and sectors of society. This relationship benefits from the knowledge produced by the university in the same way it promotes the development of Brazilian productive sector. As one of university primary functions, the provision of services has become a purpose of higher education, justifying its own existence.This research presents the provision of services as an acknowledged and regulated activity by UFMG, committed with local, regional, and national improvement; also, there is space for fulfilling the institutions academic activities and student formation. Finally, this thesis concludes that the University allows services to be provided by its teaching and technical-administrative staff provided that the requirements established by the institution are met and approved by qualified departments and that practices. Nevertheless, in practical terms, one may observe a breakaway on services related to teaching and research as well as part of the students; this fact reveals that service delivery mostly provides for the demands of the private sector, neglecting the needs of the public sector despite the mobilization of its own personel and facilities.